BIA based predictive equations for the estimation of body composition in paediatrics using deuterium dilution as reference technique: A systematic review - Suan, W.B.; Yoke, N.K. (2021)
Introduction: Childhood obesity remain as an urgent public heahh issue that needs to be concerned and addressed. Broelectric impedance analysis (BIM considered as an optimal method to assess body compositions. Many BIA predictive equations have been developed using reference methods foe assessing body composition in paediatric populations but as accuracy only applies to the population from which they have been derived Objective: To summarize and assess whether the developed BIA based predictive equations are able to accurately estimate body composition in paediatrics populations using deuterium dilution as the reference method. Methodology: The review protocol was based on Preferred Reporting Items for Systematic Reviews and Meta-analysis (WAWA) guidelines. Literature search was conducted in PubMed and Scopus database for observational studies developing an equation to estimate TRW and FFM using deuterium dilution as criterion among Paediatrics. The manual search was also conducted to find more related studies. Results: A total of 15 studies were included in this systematic review. The quality of included studies was assessed using the Effective Public Health Practice Project (EPHPPI. The majority of the equations developed were able to explain more than 80% of variance of body composition estimated. Out of 25 equations available, 16 of them were cross•vandated and showed a precise estimation of 16W and F f M. Conclusion: All 25 BIA equations Identified were precise and reasonably accurate for estimation of body Composition BIA appeared to be a valuable tool to accurately address the estimation of body composition only to the populations from which they have been derived. Continuous research using multi-component models as criterion and cross-validating developed predictive equations is needed to overcome present obstacles and further improve the estimation of paediatrics body composition.